MENINGKATKAN KAPASITAS PELAKSANA DALAM PENEGAKAN PERATURAN DAERAH DI KALIMANTAN BARAT - Syarif Imron Rosadi E.21111117 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This thesis is intended to determine policy implementation tasks Civil Service Police Unit in the province of West Kalimantan Regional Enforcement. The problem in this study is still a lot of West Kalimantan Provincial Regulation that can not be optimally upheld by the Civil Service Police Unit of West Kalimantan Province is one of the Regional Regulation  No. 8 of 2010 on Local Taxes particularly with regard to enrollment / registration and reporting the number of motor vehicles police outside the entrance to the West Kalimantan West Kalimantan. The purpose of this study was ( 1 ) to determine policy implementation tasks Civil Service Police Unit in the province of West Kalimantan Regional Regulation enforcement and ( 2 ) to mengetahuifaktor - limiting factor in the implementation of the policy. The method used in this research is descriptive qualitative analysis. The results showed that the factor Resources Civil Service Police Unit of West Kalimantan Province is still lacking, especially Human Resources both in quality and quantity. Communication in terms of coordination between the Civil Service Police Unit of West Kalimantan province with relevant agencies still need to be improved. Disposition of leadership in terms of commitment is still lacking to implement the task of implementing policy enforcement Regional Regulation. Piling Bureaucracy Civil Service Police Unit of West Kalimantan Province is quite efficient, but in the bureaucratic structure kinenrja mendokrak Civil Service Police Unit has not been Standard Operating Procedure  Regional Enforcement. In writing this essay suggested to improve the Human Resources Civil Service Police Unit in West Kalimantan Province in particular the Human Resources both in quality and quantity through technical assistance and training and education to improve the knowledge of each apparatus so as to solve the problems in the implementation of the task, especially in enforcing regulations area, improving communication and coordination with agencies / institutions to implement the Regional Enforcement, the need for a firm commitment from the leadership  to  implement  the  Regional  Enforcement  and  create  Standard  Operating Procedure  (SOP)  regional  Enforcement.Keywords :  Implementation Perda, Main Task, Enforcement Perda.